Measurement of length distribution of beta-lactoglobulin fibrils by multiwavelength analytical ultracentrifugation - Uttinger, Maximilian; Heyn, Timon R.; Jandt, Uwe; Wawra, Simon; Winzer, Bettina; Keppler, Julia K.; Peukert, Wolfgang (European Biophysics Journal, 2020)
The whey protein beta-lactoglobulin is the building block of amyloid fibrils which exhibit a great potential in various applications. These include stabilization of gels or emulsions. During biotechnological processing, high shear forces lead to fragmentation of fibrils and therefore to smaller fibril lengths. To provide insight into such processes, pure straight amyloid fibril dispersions (prepared at pH 2) were produced and sheared using the rotor stator setup of an Ultra Turrax. In the first part of this work, the sedimentation properties of fragmented amyloid fibrils sheared at different stress levels were analyzed with mulitwavelength analytical ultracentrifugation (AUC). Sedimentation data analysis was carried out with the boundary condition that fragmented fibrils were of cylindrical shape, for which frictional properties are known. These results were compared with complementary atomic force microscopy (AFM) measurements. We demonstrate how the sedimentation coefficient distribution from AUC experiments is influenced by the underlying length and diameter distribution of amyloid fibrils. In the second part of this work, we show how to correlate the fibril size reduction kinetics with the applied rotor revolution and the resulting energy density, respectively, using modal values of the sedimentation coefficients obtained from AUC. Remarkably, the determined scaling laws for the size reduction are in agreement with the results for other material systems, such as emulsification processes or the size reduction of graphene oxide sheets.
CRIS-Team Scopus Importer:2020-02-11
Keywords: Amyloid fibrils; Analytical ultracentrifugation; Atomic force microscopy; Beta-lactoglobulin; Sedimentation analysis